2002
DOI: 10.1515/cclm.2002.176
|View full text |Cite
|
Sign up to set email alerts
|

Total Iron Binding Capacity and Transferrin Concentration in the Assessment of Iron Status

Abstract: Transferrin concentration and total iron binding capacity (TIBC) are currently used to assess iron status. Although correlation between TIBC and transferrin is generally considered as good, conversion factors between the two analytes found in literature show large differences. Although the price per test is lower for TIBC, there are a number of analytical advantages of serum transferrin. Due to binding of iron to other plasma proteins (mainly albumin), TIBC methods generally overestimate the iron binding capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…Routine investigation for anaemia in Nigeria and subsaharan Africa is by examination of blood film pictures, packed cell volume and haemoglobin concentration except in some Health institutions where facility and personnel is available, additional test for iron markers are added. It has been suggested that for meaningful interpretation of iron status in human, the following iron markers are of importance: haemoglobin, PCV, serum iron, TIBC, UIBC and percent transferri saturation (Kasvosve & Delanghe, 2002;Yamanishi et al, 2003;Nwafia et al, 2006;AACC, 2009). In our earlier study, we relied on serum iron and PCV to define the iron status of HIV infected participants (Onyenekwe et al, 2008;Ukibe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Routine investigation for anaemia in Nigeria and subsaharan Africa is by examination of blood film pictures, packed cell volume and haemoglobin concentration except in some Health institutions where facility and personnel is available, additional test for iron markers are added. It has been suggested that for meaningful interpretation of iron status in human, the following iron markers are of importance: haemoglobin, PCV, serum iron, TIBC, UIBC and percent transferri saturation (Kasvosve & Delanghe, 2002;Yamanishi et al, 2003;Nwafia et al, 2006;AACC, 2009). In our earlier study, we relied on serum iron and PCV to define the iron status of HIV infected participants (Onyenekwe et al, 2008;Ukibe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…LCMV has been proposed to use a receptor in addition to α-dystroglycan 11 , but no enhancement of LCMV pseudovirus entry was observed in the presence of human TfR1, indicating that this alternative receptor is not human TfR1. Transferrin is present at micromolar concentrations in human plasma 13 . We investigated whether iron-bound (holo) transferrin, which binds TfR1 with high affinity, or apo-transferrin, which does not, could modulate the infection of MACV pseudoviruses.…”
mentioning
confidence: 99%
“…However, Tf levels are also influenced by other factors not related to iron kinetics, such as inflammation, infection, malignancy, chronic liver disease, nephrotic syndrome and malnutrition, which may cause a decrease in the values of transferrin whereas pregnancy and oral contraceptives cause an increase of its serum concentration. 45,46,[50][51][52] …”
Section: Transferrin/total Iron Binding Capacitymentioning
confidence: 99%